Presynaptic Striatal Dopaminergic Function in Atypical Parkinsonism: A Metaanalysis of Imaging Studies - Kankare, Tuomas (My University, 2021)
The purpose of this study was to determine whether striatal positron emission tomography (PET) and single-photon emission computed tomography (SPECT) imaging could be used to differentiate the atypical parkinsonian disorders multiple-system atrophy (MSA), progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS) from the typical Parkinson disease (PD) for clinical and differential diagnostic purposes. Presynaptic tracers for dopamine transporter (DAT), aromatic amino acid decarboxylase (AADC) and vesicular monoamine type 2 (VMAT2) were investigated. A metaanalysis of 35 published presynaptic dopaminergic brain imaging studies of parkinsonian disorder patients and healthy controls was performed. PubMed was screened for eligible studies, and studies that fulfilled inclusion criteria determined by the study group were identified and included. Available striatal tracer binding values, disease severity scores as well as data concerning imaging methodology were extracted manually from the included studies. Collected data was synthesized using Meta-Essentials, with a statistical significance cut-off at 2-tailed P<0.05. Hedges g was used to estimate effect size in group comparisons. The data was screened for heterogeneity, and quality evaluation was performed using the Ottawa-Newcastle Scale. Key results from the synthesis showed a statistically significant difference in striatal DAT binding between PSP and PD, while PD and MSA-C or CBS did not demonstrate a significant difference. Caudal, but not putaminal DAT binding was significantly different between PD and MSA with predominant parkinsonism (MSA-P). A further significant DAT binding difference of 31.4% was found between the atypical parkinsonian syndromes PSP and MSA with predominant cerebellar ataxia (MSA-C). Clinical MSA subtypes MSA-C and MSA-P showed a 40.6% difference in DAT binding. The meta-analysis demonstrated a lower presynaptic dopaminergic function in PSP compared to both PD and MSA-P as measured by DAT binding, which may be diagnostically significant. The study provides evidence for the loss of caudate-to-putamen dopaminergic deficit gradient in MSA compared to PD.